The relationship between methane transport to the atmosphere and the decay of the Kara Sea ice cover: satellite data for 2003–2019 - L. N. Yurganov (Лëд и снег)
Satellite spectrometers operating on the outgoing long-wave IR (thermal) radiation of the Earth and placed in sunsynchronous polar orbits provide a wealth of information about Arctic methane (CH4) year-round, day and night. Their data are unique for estimating methane emissions from the warming Arctic, both for land and sea. The article analyzes concentrations of methane obtained by the AIRS spectrometer in conjunction with microwave satellite measurements of sea ice concentration. The data were filtered for cases of sufficiently high temperature contrast in the lower atmosphere. The focus is on the Kara Sea during autumn-early winter season between 2003 and January 2019. This sea underwent dramatic decline in the ice cover. This shelf zone is characterized by huge reserves of oil and natural gas (~90% methane), as well as presence of sub-seabed permafrost and methane hydrates. Seasonal cycle of atmospheric methane has a minimum in early summer and a maximum in early winter. During last 16 years both summer and winter concentrations were increasing, but with different rates. Positive summer trends over the Kara Sea and over Atlantic control area were close one to another. In winter the Kara Sea methane was growing faster than over Atlantic. The methane seasonal cycle amplitude tripled from 2003 to 2019. This phenomenon was considered in terms of growing methane flux from the sea. This high trend was induced by a fast decay of the sea ice in this area with ice concentrations dropped from 95 to 20%. If the current Arctic sea cover would decline further and open water area would grow then further increase of methane concentration over the ocean may be foreseen.